COMPARISON OF CONVENTIONAL AND SPREAD SPECTRUM SIGNALS TIME OF FLIGHT ERROR CAUSED BY NEIGHBORING REFLECTIONS - Svilainis, Linas; Aleksandrovas, Arturas; Lukoseviciute, Kristina; Eidukynas, Valdas (International Journal of Computing, 2014)
Performance comparison of conventional and spread spectrum signals in Time of Flight estimation is given. Ultrasonic measurement under multiple reflections condition is analyzed. It was indicated that if two reflections are in close proximity the neighboring signal induces energy leak into its opponent signal. Due to such situation ToF estimate is obtained with bias error. Narrow signals like single rectangular pulse, should suffer less from the aforementioned phenomena. But use of spread spectrum signals is preferred thanks to their compressibility. It was hypothesized that such long signals will have worse bias error due to neighbor reflection. Goal of the investigation was to compare the performance in multiple reflections environment in Time of Flight estimation for classical signals and spread spectrum signals. Investigation revealed that spread spectrum signals have better performance in a sense of bias error caused by neighboring reflection.